An Explorative Study of Indonesian Traditional Cheese 'Dangke' as High Protein Food from Enrekang, South Sulawesi - Sa'pang, Mertien; Salam, Abdul; Harna, Harna; Rahmayanti R, Andi; Seprianto, Seprianto; Nurmalasari, Mieke; Ruhmayanti, Nur Ayu; Swamilaksita, Prita Dhyani (Poltekita : Jurnal Ilmu Kesehatan, 2023)
This study aimed to examine the historical and cultural values of dangke as a traditional food, its potential as a source of animal protein, and the methods of its preparation and presentation. This qualitative descriptive study used in-depth interviews with key informants, focus group discussions with primary and supporting informants, and observation to collect data. The findings of this study indicate that dangke, which was originally made from buffalo milk and enriched with enzymes from papaya sap, reflects the culinary heritage of the Massenrempulu tribe in Enrekang Regency, South Sulawesi. However, the limited supply of buffalo milk has led to the modification of dangke using cow's milk in some parts of Enrekang. Historically, dangke has been served with rice or "pulu mandoti" to guests since the colonial era. The origin of the term "dangke" itself has roots in the Dutch language, possibly from the expression "dank je wel" (thank you) used by Dutch soldiers after tasting this delicious dish. In addition, previous studies have shown that dangke has a high protein content, making it a valuable food source to support the diversification of animal protein sources. In conclusion, dangke has a high cultural value for the people of Enrekang and is a traditional food with high nutritional value, especially in terms of protein content.